Determinants of Language Development in 18-Month-Old Children within Primary Healthcare Settings - Trakultip, Piyaphan; Wangwonsin, Artittaya; Jariya, Wutthichai (Journal of primary care & community health, 2025)
Language development during the first 2 years is crucial for cognitive and social growth. The purpose of this study was to assess receptive language (RL) and expressive language (EL) development and associated factors in 18-month-old Thai children. This cross-sectional study was conducted from September 2024 to February 2025. Multistage sampling was applied to recruit 1150 participants who were parents or primary caregivers of 18-month-old children. Data were collected using structured questionnaires and the Developmental Surveillance and Promotion Manual, a standardized national tool. Binary logistic regression was used to analyze associations between child, parental, and healthcare access factors and language development. Overall, 88.7% and 85.6% of children had age-appropriate RL and EL development, respectively. After adjusting for covariates, high parental knowledge and high parental behaviors in language development were significantly associated with both age-appropriate RL development (AOR = 2.122, 95% CI = 1.338-3.364 and AOR = 2.251, 95% CI = 1.396-3.628, respectively) and age-appropriate EL development (AOR = 2.452, 95% CI = 1.618-3.718 and AOR = 1.892, 95% CI = 1.210-2.960, respectively). Access to anemia screening services at 6 to 12 months was also significantly associated with both age-appropriate RL development (AOR = 1.700; 95% CI = 1.104-2.617) and age-appropriate EL development (AOR = 2.026; 95% CI = 1.384-2.967). Parental and healthcare access factors were significant determinants of language development. Improving parental competencies and integrating language development surveillance and preventive healthcare at primary care settings could be valuable strategies for promoting language development in early childhood.